2022
DOI: 10.5603/cj.a2020.0036
|View full text |Cite
|
Sign up to set email alerts
|

Risk of left atrial appendage thrombus in patients with atrial fibrillation and chronic kidney disease

Abstract: Background: Atrial fibrillation (AF) and chronic kidney disease (CKD) are associated with an increased risk of ischemic stroke. The aim of this study was to compare the clinical characteristics, the incidence of left atrial appendage (LAA) thrombus and its predictors, and spontaneous echo contrast (SEC) in a population of patients with AF depending on estimated glomerular filtration rate (eGFR) values. Methods: This study included 1962 patients who underwent transesophageal echocardiographic examination (TEE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
7
0
5
Order By: Relevance
“…In the academic department, all patients have TEE performed routinely before direct current cardioversion of AF or catheter ablation for AF (pulmonary vein isolation) excluding those admitted for cardioversion for emergency indications, as described previously 2,6 . In the military hospital, preprocedural TEE was performed in case of any doubt regarding the efficacy of oral anticoagulation (OAC) or patient's compliance 7,8 . In both departments, TEE was conducted within 48 hours prior to the scheduled procedure (usually directly or a few hours before the procedure).…”
Section: Methodsmentioning
confidence: 99%
“…In the academic department, all patients have TEE performed routinely before direct current cardioversion of AF or catheter ablation for AF (pulmonary vein isolation) excluding those admitted for cardioversion for emergency indications, as described previously 2,6 . In the military hospital, preprocedural TEE was performed in case of any doubt regarding the efficacy of oral anticoagulation (OAC) or patient's compliance 7,8 . In both departments, TEE was conducted within 48 hours prior to the scheduled procedure (usually directly or a few hours before the procedure).…”
Section: Methodsmentioning
confidence: 99%
“…Although neither the 2020 guidelines of the European Society of Cardiology [ 4 ] nor the 2021 European Heart Rhythm Association practical guide on the use of NOACs [ 16 ] provide clear recommendations on the choice of NOAC in specific clinical situations, in our real-life AF/AFl population, we observed a preference for apixaban in patients with the highest bleeding risk and the worst renal function (and a preference for rivaroxaban and dabigatran in those with the lowest bleeding risk, with VKA prescribed in the “intermediate” group): patients on apixaban were the oldest (median age: 71 years vs. 68 years on VKA vs. ~66 years on rivaroxaban and dabigatran), more often had a history of previous bleeding (7.0% vs. 3.5% on VKA and ~3% on rivaroxaban and dabigatran) or anemia (19% vs. 22% on VKA vs. 12% on rivaroxaban and 15% on dabigatran) and more often had GFR < 50 mL/min (18% vs. 15% on VKA vs. ~8% on rivaroxaban and dabigatran). At the same time, patients on apixaban had the highest thromboembolic risk determined by both the highest median CHA 2 DS 2 -VASc score (4 vs. 3 on VKA, rivaroxaban and dabigatran) and the worst renal function [ 17 , 18 ]. This, together with more frequent prescription of reduced doses, could account for the higher prevalence of LA thrombus in apixaban-treated patients compared to rivaroxaban- and dabigatran-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced kidney disease was associated with a higher risk of stroke, death, and bleeding. Some studies identified renal dysfunction to be an important predictor of LAAT, enhancing the prognostic value of the CHA2DS-VASc score [2,3]. Impaired renal function was a predictor of LAAT only in men.…”
Section: Discussionmentioning
confidence: 99%
“…The CHADS2 and CHA2DS2-VASc scores are used for the assessment of thromboembolic risk in patients with nonvalvular AF. The CHA2DS2-VASc-RAF score additionally included the type of AF and renal dysfunction as LAAT predictors, which appeared to improve thromboembolic risk stratification [2][3][4]. Despite optimal treatment with vitamin K antagonists and the currently preferred non-vitamin K oral antagonists (NOACs), LAAT still develops in 2% to 10% of patients on anticoagulant treatment [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%